2014
DOI: 10.1007/s11060-014-1591-2
|View full text |Cite
|
Sign up to set email alerts
|

Symptoms and medication management in the end of life phase of high-grade glioma patients

Abstract: During the end of life (EOL) phase of high-grade glioma (HGG) patients, care is primarily aimed at reducing symptom burden while maintaining quality of life as long as possible. In this study, we evaluated the prevalence of symptoms and medication management in HGG patients during the EOL phase. We analyzed disease-specific symptoms, general EOL symptoms, symptom frequency, and medication use at 3 months and 1 week before death in a cohort of 178 HGG patients, based on questionnaires completed by physicians re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
63
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(65 citation statements)
references
References 39 publications
1
63
0
1
Order By: Relevance
“…The most frequent treatment for headache in glioma patients is the use of corticosteroids (56-87%) 6,7 , usually dexamethasone in conjunction with gastric protection (81-86%). 7,8 Dexamethasone once a day is the preferred corticosteroid based on side-effect profile, but still has a wide range of side-effects (e.g., Cushing effect, muscle weakness and diabetes mellitus), increasing with higher dose and longer duration of treatment.…”
Section: Pain/headachementioning
confidence: 99%
See 1 more Smart Citation
“…The most frequent treatment for headache in glioma patients is the use of corticosteroids (56-87%) 6,7 , usually dexamethasone in conjunction with gastric protection (81-86%). 7,8 Dexamethasone once a day is the preferred corticosteroid based on side-effect profile, but still has a wide range of side-effects (e.g., Cushing effect, muscle weakness and diabetes mellitus), increasing with higher dose and longer duration of treatment.…”
Section: Pain/headachementioning
confidence: 99%
“…These respiratory symptoms have been reported in 12-23% of brain tumour patients in the last weeks of life and may severely affect a peaceful process of dying, particularly disturbing caregiver and family. 6,65 Treatment may involve change of posture to drain saliva, or medication with injectable scopolamine, an anticholinergic agent. A Cochrane review, however, concluded that there was no evidence for the benefit of any pharmacological intervention for the treatment of death rattle.…”
Section: Nutrition Hydration Respirationmentioning
confidence: 99%
“…Disease-specific symptoms in the last weeks of the EOL phase include epilepsy, headache, drowsiness, dysphagia, and cognitive disturbances like agitation and delirium [41,45,46,47]. These symptoms occur more often in glioma patients than general EOL symptoms as commonly seen in patients with systemic cancers, such as fatigue, pain, nausea, constipation and dyspnea [41,47,48]. Glioma patients with more symptoms in the week preceding death experience a lower quality of care compared to patients with fewer symptoms [48].…”
Section: Possible Role Of Acp In the Treatment Of The Main Symptommentioning
confidence: 99%
“…These symptoms occur more often in glioma patients than general EOL symptoms as commonly seen in patients with systemic cancers, such as fatigue, pain, nausea, constipation and dyspnea [41,47,48]. Glioma patients with more symptoms in the week preceding death experience a lower quality of care compared to patients with fewer symptoms [48]. In addition, motor disability and cognitive decline negatively contribute to the patient’s quality of life and social well-being.…”
Section: Possible Role Of Acp In the Treatment Of The Main Symptommentioning
confidence: 99%
See 1 more Smart Citation